Nilai-Nilai Religius dalam Novel ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œBulan Terbelah di Langit AmerikaÃƒÂ¢Ã¢â€šÂ¬Ã‚Â Karya Hanum Salsabiela Rais dan Rangga Almahendra - Nurul Fatimah (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2017)
One of literary work in the novel that are phenomenal at this time is novel titled ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œSplit Moon in the Sky AmericaÃƒÂ¢Ã¢â€šÂ¬Ã‚Â by Hanum Salsabiela Rais and Rangga Almahendra. Genre of the novel is very different from other novels. Novel that reveals the mystery of 9/11 or often called black Tuesday able to arouse the readerÃƒÂ¢Ã¢â€šÂ¬Ã¢â€žÂ¢s heart. Without Islamic. Will world beautiful? All answered in this novel. It also presents a novel religious values associated with the god and among the others. So the experts looked at the novelÃƒÂ¢Ã¢â€šÂ¬Ã¢â€žÂ¢s literary quality because not only giving entertainment but also inculcating religious value are easily understood and implemented by the reader in everyday life